Peranan Balai Lelang Swasta Terhadap Pelaksanaan Lelang Objek Hak Tanggungan - Fatma Fauzia (Recital Review, 2023)
If the implementation of the credit agreement has developed into a non-current credit, the Bank must seek credit rescue. One form of credit rescue that can be done is the execution of collateral. In practice, the auction of execution of mortgage rights is carried out through an auction hall registered with the State Property and Auction Service Office (KPKNL).  This research focuses on how the implementation of the auction of the execution of the object of mortgage rights through the private auction hall, how the role and responsibility of the private auction hall towards the implementation of the auction of the execution of the object of mortgage rights and what are the obstacles encountered in the implementation of the auction of the execution of the object of mortgage rights through the private auction hall. The results of this study are that the seller or owner of the goods who intends to sell goods by auction through the Auction Hall or the Class II Auction Officer's Office, must submit a written request for auction to the Leader of the Auction Hall or Class II Auction Officer, accompanied by auction requirement documents in accordance with the type of auction. The Auction Center or KPKNL is responsible for the formal truth, while the material truth is the responsibility of the seller or owner of the goods. The results of the next study are the obstacles encountered in the implementation of the auction, including the absence of auction enthusiasts, the collateral has not been registered, the selling value of the collateral object is smaller than the amount of the debtor's debt.